2008
DOI: 10.1002/hbm.20652
|View full text |Cite
|
Sign up to set email alerts
|

Regional networks underlying interhemispheric connectivity: An EEG and DTI study in healthy ageing and amnestic mild cognitive impairment

Abstract: Interhemispheric coherence derived from electroencephalogram (EEG) recordings is a measure of functional interhemispheric connectivity. Diffusion tensor imaging (DTI) determines the integrity of subcortical fiber tracts. We studied the pattern of subcortical fiber tracts underlying interhemispheric coherence and its alteration in 16 subjects with amnestic mild cognitive impairment (MCI), an at risk syndrome for Alzheimer's disease, and 20 cognitively healthy elderly control subjects using resting state EEG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 97 publications
8
70
0
1
Order By: Relevance
“…Moreover, virtually none of those methods incorporate biophysical knowledge about AD (but see [37]); detailed mathematical models of the pathology of AD, in conjunction with EEG data analysis, may help us to improve the diagnosis of AD. Along the same lines, one may expect further improvement by combining EEG with other imaging modalities, such as MRI (see, e.g., [31][32][33]), dMRI [34], TMS [35], and SPECT [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, virtually none of those methods incorporate biophysical knowledge about AD (but see [37]); detailed mathematical models of the pathology of AD, in conjunction with EEG data analysis, may help us to improve the diagnosis of AD. Along the same lines, one may expect further improvement by combining EEG with other imaging modalities, such as MRI (see, e.g., [31][32][33]), dMRI [34], TMS [35], and SPECT [36].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed largely convergent results (23)(24)(25)(26), indicating that at the regional as well as at the connectome (27,28) level, the strength of FC is positively correlated with the strength of SC, when direct or indirect SC is present and measurable. There is further evidence that there is significant cor-relation between structural white matter coherence and EEG FC in healthy controls and patients with amnesic mild cognitive impairment (29).…”
mentioning
confidence: 95%
“…Applying DTI analyses with voxelwise TBSS, 22 an increasing number of contributions described the damage of long interhemispheric and intrahemispheric white matter tracts with homogeneously oriented fibers (ie, genu or splenium of the corpus callosum, superior longitudinal fasciculus, cingulus) and, more rarely, in frontal, parietal, and temporal white matter in patients with MCI compared with healthy controls. [23][24][25][26][27][28][29][30][31] The biologic relevance of the description of MCI subtypes is still a challenging issue. In particular, it is unclear whether the neuropsychologic definition of these subtypes corresponds to distinct patterns of brain compromise.…”
mentioning
confidence: 99%